PROFITABILITAS SEBAGAI PEMODERASI PENGARUH GOOD CORPORATE GOVERNANCE PADA NILAI PERUSAHAAN - Permatasari, Luh Wulan; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
This study was conducted to determine the role of profitability in relation to corporate governance and firm value. This research was conducted in the Indonesia Stock Exchange. The sampling method used purposive sampling, the total sample of 85 observations for five years of research. Data collection methods in this study using a non-participant observation method. The analysis technique used is moderated regression analysis. Based on the results of the study found that the profitability able to moderate the influence of corporate governance on firm value. Increasing GCG score means the higher of the firm value, especially for companies that have high profitability. The existence of profitability will strengthen the positive influence between corporate governance and firm value.
Keywords: good corporate governance, firm value, profitability